Conjugated precipitation of twin-related α and Ti2Cu phases in a Ti–25V–3Cu alloy. (1st February 2015) - Ng, H.P.; Nandwana, P.; Devaraj, A.; Samblanet, M.; Nag, S.; Nakashima, P.N.H.; Meher, S.; Bettles, C.J.; Gibson, M.A.; Fraser, H.L.; Muddle, B.C.; Banerjee, R.
Abstract: The formation of conjugated precipitates in a ternary Ti–25V–3Cu (wt.%) (Ti–24.4V–2.3Cu (at.%)) alloy subjected to isothermal aging at 500 °C was investigated in this study. X-ray diffraction confirms that the equilibrium precipitates in the alloy are hexagonal α phase and body-centered-tetragonal (bct) Ti2 Cu intermetallic compound. These precipitates are composed of two geometrically symmetrical components, which are verified by transmission electron microscopy (TEM) to be twin-related variants of α and Ti2 Cu phases. Atomic-level characterizations incorporating high-resolution TEM and atom probe tomography were used to investigate the early-stage nucleation process of the precipitates. The results reveal that precipitation occurs heterogeneously on plate-like (or disc-like) metastable Cu-enriched GP zones that preferentially inhabit {1 1 0}β planes. Crystallographic orientation analyses suggest that the Ti2 Cu phase is related to the matrix via a definite orientation relationship of ( 0 1 ¯ 3 ) T i 2 Cu ‖ ( 0 1 1 ) β and [ 1 0 0 ] T i 2 Cu ‖ [ 1 0 0 ] β, while the growth of the α phase is governed by the Potter's OR such that ( 1 1 ¯ 0 1 ) α ‖ ( 0 1 1 ) β and [ 1 1 2 ¯ 0 ] α ‖ [ 1 1 ¯ 1 ] β . ( 0 1 ¯ 3 ) Ti 2 Cu and ( 1 1 ¯ 0 1 ) α are the twin planes of the respective phases. In spite of highly distinct crystal structures, the conjugated α and Ti2 Cu phases attain a nearly perfect lattice correspondence along certain crystallographic planes, which results in a low interfacial energy configuration and favours the co-development of these phases.